PENGARUH SUPLEMENTASI TEPUNG KROKOT (Portulaca oleracea) TERHADAP TOTAL SEL DARAH PUTIH DAN DIFERENSIAL SEL DARAH PUTIH KAMBING JAWARANDU (Capra aegagrus hircus) - Fani Setiawan; Erwanto Erwanto; Sri Suharyati; Siswanto Siswanto (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
The purpose of this study was to determine the effect of Purslane flour on total white blood cells, and white blood cell differential in Jawarandu goats. This research was conducted from February until March 2021 in the Livestock Group of Rambon Asri, Rejo Asri Village, Seputih Raman District, Lampung Tengah Regency, Lampung Province. Examination of white blood cells and white blood cell differential was carried out at the Lampung Veterinary Disease Investigation Center. The experimental design used was a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments were basal ration (P0), basal ration with 5% Purslane flour supplementation (P1), basal ration with 10% Purslane flour supplementation (P2), and basal ration with 15% Purslane flour supplementation (P3). The data obtained were analyzed using analysis of variance with a significance level of 5% and if a significant effect was obtained, it was continued tested with orthogonal polynomials. The results showed that purslane flour supplementation had a significant effect (P<0.05) on total neutrophils and a very significant effect (P<0.01) on total white blood cells and lymphocytes, but had no significant effect (P>0.05) against monocytes. The best dose of purslane flour supplementation which was optimum for white blood cells, lymphocytes, and neutrophils was 3.01% kg/DM (dry matter) ration, 8.34% kg/DM ration, and 10.51% kg/DM ration, respectively. Keywords: Jawarandu goat, Purslane flour, White blood cell, White blood cells differential